2021
DOI: 10.3390/ijms22010428
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Effects on Guard Cell Proteome in Chenopodium quinoa

Abstract: Epidermal fragments enriched in guard cells (GCs) were isolated from the halophyte quinoa (Chenopodium quinoa Wild.) species, and the response at the proteome level was studied after salinity treatment of 300 mM NaCl for 3 weeks. In total, 2147 proteins were identified, of which 36% were differentially expressed in response to salinity stress in GCs. Up and downregulated proteins included signaling molecules, enzyme modulators, transcription factors and oxidoreductases. The most abundant proteins induced by sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 71 publications
4
14
0
Order By: Relevance
“…In line with the above, the possibility of low salinity-induced modulation of the photosynthetic carbon fixation could be ruled out. The optimal performance of P. antidotale in terms of photosynthetic capacity at low salinity was consistent in published results ( Koyro et al, 2013 ; Hussain et al, 2015 , 2020 : Rasouli et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…In line with the above, the possibility of low salinity-induced modulation of the photosynthetic carbon fixation could be ruled out. The optimal performance of P. antidotale in terms of photosynthetic capacity at low salinity was consistent in published results ( Koyro et al, 2013 ; Hussain et al, 2015 , 2020 : Rasouli et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Given the wealth of reports on quinoa molecular characterization, it is somewhat surprising that its proteome has received only limited attention. In fact, this study is among the few manuscripts that provide features of quinoa proteome by large-scale proteomic approaches [ 11 , 12 , 13 ] and the first focused on its mitochondrial proteome, as well as the first quinoa proteome investigation relying on systems biology and graph theory.…”
Section: Discussionmentioning
confidence: 99%
“…For this goal, we combined proteomic and systems biology approaches based on network analysis [ 10 ]. To date, few works have focused on quinoa proteome by shotgun approaches [ 11 , 12 , 13 ], while none have relied on protein–protein interaction (PPI) and/or protein co-expression (Co-Exp) network analysis. This is mainly due to the lack of a quinoa PPI network model and accurate functional annotations [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Rasouli et al 44 , salinity altered the physical properties of epidermic cells, specifically in the guard cell wall. In their study they demonstrated that the cell-wall-modifying enzymes such as acetyl- and methyl-esterifications esterases of pectin were upregulated in the epidermic cells of the halophyte Chenopodium quinoa.…”
Section: Discussionmentioning
confidence: 99%